Adolescent mental health in sub-Saharan Africa: crisis? What crisis? Solution? What solution? - Claire Hart; Shane A. Norris (Global Health Action)
Addressing adolescent mental health care across sub-Saharan Africa faces numerous challenges, including underfunded public health systems, a shortage of mental health professionals, barriers to access, and pervasive stigma. Untreated adolescents often experience worsening symptoms, academic and social difficulties, physical health risks, and engage in risky behaviours. Early detection and appropriate treatment of common mental health conditions can support adolescents in developing robust social and emotional foundations and enhancing their mental well-being. Ensuring adolescents receive the mental health care required for healthy development depends on collaborative, evidence-based solutions that consider the contextual challenges of sub-Saharan Africa. Innovative community-based solutions to mental health services may significantly improve accessibility and support adolescents close to their homes and schools. For example, co-creation and peer-delivered interventions with professional supervision may enhance uptake and reduce stigma. This short article adds to the current debate arguing for working with communities and implementing community mental health services for common mental health conditions. Sensitivity to community-specific challenges and building referral networks are crucial for effective care. Investing in these strategies, alongside increasing mental health literacy, could lead to affordable and significant interventions to address adolescent mental health.